The role of knowledge creation, absorption and acquisition in determining national competitive advantage. (April 2022) - Ge, Shuang; Liu, Xielin
Abstract: Knowledge has been considered a key factor in countries' catch-up of competitive advantage. However, few studies have deeply analyzed the complex interaction effect of internal technological capabilities and external knowledge acquisition, and the influence of the institutional environment is often ignored. In this paper, we integrate the knowledge-based view with both the new growth theory and the institution-based view, empirically test the validity of our competitive theoretical framework using the panel data of 29 developing countries and 32 developed countries from 1995 to 2018. The results show that, in countries at different stages of development, internal technological capabilities (knowledge creation capability and knowledge absorption capability) and external knowledge acquisition (external technological knowledge and market information knowledge) have different mechanisms of action, constraints and interaction effects. The findings suggest that countries need to make different catch-up strategies according to their stage of national development. Highlights: Enhancing knowledge creation capability facilitates catch-up of national competitive advantage. Acquiring external technological knowledge has an inverted U-shaped effect on catch-up of national competitive advantage. Knowledge absorption capability positively moderates the inverted U-shaped effect of external technological knowledge on CCA. External technological knowledge and internal technological capability in developing countries have a synergistic effect. Developed countries need to pay attention to the antagonistic effect of knowledge leakage and knowledge creation. Moderating effect of IPR varies with the development of countries.